Models and Challenges of Coordination in Regional Disaster Management - Musdah, Erwin; Fattah, Sulaeman; Narwis, Sudarmi (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2022)
Disaster is a complex problem that requires coordination with many parties. The results of previous studies regarding disaster management in Wajo indicated that there were coordination problems in disaster management in Wajo. This study aims to explain the coordination of disaster management in Wajo from the perspective of the models and challenges of disaster management in Wajo. This study uses a qualitative approach with the Gadamerian hermeneutic method to find the meaning of coordination texts in the context of pre-disaster management. Data collection was carried out through document analysis and interviews. The results of the study revealed that the coordination of disaster management in Wajo was running well at the disaster preparedness stage but was still not optimal at the pre-disaster stage. We found three meanings of coordination in disaster management in Wajo. First, coordination because of their awareness of the limitations they have. Second, coordination serves as fulfillment of the requirements of sponsorship activities. Third, coordination is an innovation to overcome problems. Coordination in Wajo is hampered by the actors' interpretation of the subject and object of disaster management coordination.